Analisis Penerapan Projek Penguatan Profil Pelajar Pancasila Dimensi Mandiri pada Siswa Kelas IV Sekolah Dasar Negeri Ngandul 2 Kecamatan Sumberlawang, Kabupaten Sragen Tahun Pelajaran 2023/2024 - Larasati, Anggita; Mahendra, Moefty; Sutrisno, Tri (UNIVERSITAS SERAMBI MEKKAH, 2024)
The aim of this research is to analyze the implementation of the Independent Dimension of the Pancasila Student Profile Strengthening Project, to find out the obstacles in implementing the Independent Dimension of the Pancasila Student Profile Strengthening Project and to find out solutions to the obstacles in implementing the Independent Dimension of the Pancasila Student Profile Strengthening Project in class IV students at the Ngandul State Elementary School. 2 Sumberlawang District, Sragen Regency, Academic Year 2023/2024. This research method uses descriptive qualitative methods. The time of the research was in May 2024, the location was at Ngandul 2 State Elementary School, Ngandul Village, Sumberlawang subdistrict, Sragen district. The research subjects consisted of 15 fourth grade students and the class teacher. Data collection methods were observation, interviews and documentation. Test validity using source triangulation. The data analysis technique uses interactive data analysis techniques. The results of the research concluded that the implementation of the Project for Strengthening the Profile of Pancasila Students with Independent Dimensions for students was going quite well in the project, for students who were less independent in their learning, the constraints or barriers of the Project for Strengthening the Profile of Pancasila Students with Independent Dimensions were students' lack of understanding of learning, lack of understanding by teaching staff regarding the project to strengthen the profile of Pancasila students, has low human resources and differences in student characteristics, the solution to these obstacles is that teachers can provide guidance to students, students need to have self-awareness of their independence and there must be support from their environment.